Perjuangan Perempuan dalam Kumpulan Cerpen Parade yang Tak Pernah Usai: Kajian Feminisme Liberal Naomi Wolf - Ulva, Aulia; Juanda, Juanda; Saguni, Suarni Syam (Neologia: Jurnal Bahasa dan Sastra Indonesia, 2025)
The purpose of this research is to depict the struggles of women in the short story collection Parade yang Tak Pernah Usai. This research is descriptive qualitative in nature. The data collection techniques used are observation and documentation, applying reading and note-taking methods. The study involves identifying, clarifying, interpreting, and describing the struggles of women in the short story collection Parade yang Tak Pernah Usai based on the Liberal Feminism theory of Naomi Wolf. The research findings indicate that the author highlights the struggles of female characters to achieve equal roles, the right to determine their own fate, to express their experiences, and to receive anything without exception, just like men.